2009
DOI: 10.1126/science.1170027
|View full text |Cite
|
Sign up to set email alerts
|

Helical Nanofilament Phases

Abstract: In the formation of chiral crystals, the tendency for twist in the orientation of neighboring molecules is incompatible with ordering into a lattice: Twist is expelled from planar layers at the expense of local strain. We report the ordered state of a neat material in which a local chiral structure is expressed as twisted layers, a state made possible by spatial limitation of layering to a periodic array of nanoscale filaments. Although made of achiral molecules, the layers in these filaments are twisted and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
432
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(458 citation statements)
references
References 23 publications
21
432
1
4
Order By: Relevance
“…No other periodicity up to 15 nm length scales can be found. The correlation length x ¼ 2/Dq ¼ 21 nm corresponding to a domain size wB2, xB40 nm (Francescangeli et al 20 ), is in accordance with the typical width of the helical nanofilaments found by FFTEM 6 . Polarizing optical microscopy textures of 5-10 mm films are grainy dark blue indicating low birefringence in the B4 phase.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…No other periodicity up to 15 nm length scales can be found. The correlation length x ¼ 2/Dq ¼ 21 nm corresponding to a domain size wB2, xB40 nm (Francescangeli et al 20 ), is in accordance with the typical width of the helical nanofilaments found by FFTEM 6 . Polarizing optical microscopy textures of 5-10 mm films are grainy dark blue indicating low birefringence in the B4 phase.…”
Section: Resultssupporting
confidence: 57%
“…2a) that varies in the short range 100-120 nm from one homologue to another. The period h of the families of fringes equals half pitch of the nanofilaments found in FFTEM experiments by Hough et al 6 , indicating that the filaments in Fig. 2 grow parallel to the substrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chirality of fd wt rods is left handed 26,27 , which imposes a well-defined handedness onto the colloidal membrane edge. This complex edge behaviour is one specific manifestation of a very general packing frustration present whenever chiral molecules are forced to assemble into 2D smectic-like sheets [28][29][30][31] .…”
Section: Resultsmentioning
confidence: 99%